2013
DOI: 10.1088/0741-3335/55/6/065006
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-relativistic electrostatic Bernstein waves

Abstract: A new general form of the dispersion relation for electrostatic Bernstein waves in ultra-relativistic pair plasmas, characterized by1, is derived in this paper. The parameter S p = a 0 /ω p , where 0 is the rest cyclotron frequency for electrons or positrons and ω p is the electron (or positron) plasma frequency, plays a crucial role in characterizing these waves. In particular, S p has a restricted range for permitted wave solutions; this range is effectively unlimited for classical plasmas, but is significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…It has been widely observed that Ohmic energy confinement in tokamaks increases linearly with electron density, and then saturates at a critical density [1,2,3,4,5,6,7,8,9,10,11,12,13,14,15]. An example of this behavior is shown in Fig.1 was obtained from a shot by shot scan of the electron density in 5.2 T, 0.81 MA (q 95 = 4.3) plasmas from Alcator C-Mod [13].…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…It has been widely observed that Ohmic energy confinement in tokamaks increases linearly with electron density, and then saturates at a critical density [1,2,3,4,5,6,7,8,9,10,11,12,13,14,15]. An example of this behavior is shown in Fig.1 was obtained from a shot by shot scan of the electron density in 5.2 T, 0.81 MA (q 95 = 4.3) plasmas from Alcator C-Mod [13].…”
Section: Introductionmentioning
confidence: 91%
“…An example of this behavior is shown in Fig.1 was obtained from a shot by shot scan of the electron density in 5.2 T, 0.81 MA (q 95 = 4.3) plasmas from Alcator C-Mod [13]. The energy confinement time was determined from the kinetic profiles during the steady state portion of each discharge.…”
Section: Introductionmentioning
confidence: 99%
“…One example would be a change of wave propagation from the electron diamagnetic drift direction (electron drift waves) to the ion direction (ion drift waves or ITG modes) as the density exceeds a critical threshold [22]. Such a change from TEM (or ETG) to ITG turbulence domination has been invoked to explain the transition in global energy confinement from the linear (neo-Alcator) to saturated Ohmic confinement regimes [23]. In fact, the reversal density of ∼0.8×10 20 /m 3 for 5.4 T, 0.8 MA discharges (Fig.10) is very close to the density separating the linear energy confinement regime from the saturated confinement regime for Ohmic discharges (Fig.1 of [23]).…”
Section: Turbulence Changes During Reversalsmentioning
confidence: 99%
“…There are several longstanding mysteries in tokamak research: explanation of the observed edge up/down impurity density asymmetries [1,2,3,4], the mechanism governing the linear Ohmic confinement (LOC, also known as neo-Alcator scaling) regime and the transition to saturated Ohmic confinement (SOC, L-mode) [5,6,7,8,9,10,11,12,13,14,15,16,17], and the underlying cause of 'non-local electron heat transport' following cold pulses [18,19,20,21,22,23,24,25,26,27]. A recent mystery to add to this list is the rotation reversal or inversion process [28,29,30,31,32,33], in which the core toroidal rotation abruptly switches direction, with negligible effect on other macroscopic plasma parameters.…”
Section: Introductionmentioning
confidence: 99%